(untitled) (Eurasian Medical Research Periodical, 2023)
Dystrophic changes were observed in the myocardium of the heart wall of rat pups born from mothers in the state of experimental diabetes mellitus. The observed changes reached a maximum by the 14th day of the study, manifesting as perivascular and interstitial lymphohistiocytic infiltrate